Solid-state biosensors and field-effect transistor devices based on organic semiconductors - Mello, Hugo José Nogueira Pedroza Dias (2019)
Biosensors based on solid-state field-effect transistor as transducer stage using organic semiconducting materials as sensing stage have been developed. Polyaniline thin films galvanostatic electrodeposited were fabricated. Varied electrodeposition parameters were tested, such as deposited charge, current density, deposition time and monomer concentration, besides the tests of a polymeric blend composed of polyaniline and polypyrrole and tested as pH potentiometric extended gate field-effect transistor sensor. Then, biosensors were produced using the one-step electrochemical immobilization process to obtain thin polyaniline films with entrapped glucose oxidase and urease enzymes, to detection of glucose and urea, respectively. The optimized films presented sensitivity, linearity and detection range to glucose of 14.6 ± 0.4 mV/decade, 99.8 % and from 10-4 mol/L to 10-1 mol/L. Two different biosensors were produced based on the enzymatic catalysis of urea with selectivity to ammonium or hydroxyl ions. For ammonium ion selective films, the sensor presented sensitivity, linearity and detection range of 14.7 ± 0.9 mV/decade, 98.2 % and from 10-5 mol/L to 10-1 mol/L. For the hydroxyl ion selective film, the same parameters were 7.4 ± 0.5 mV/decade, 98.1 % and from 10-5 mol/L to 10-1 mol/L. The same functionalized polyaniline thin films were used in optical and conductometric biosensors due to the polyelectrochromic characteristic of the material. Improvement of the field-effect system was possible with the multimodal array of enzymatic biosensor. The device was built using different enzymatic sensing stages connected to the extended gate field effect transistor. The system decreased the time needed to make distinct measurements, showed good response to the variation in solutions pH, to the presence of the reference film and to injection of target analyte in solution in real time measurement. The electrolyte gated organic field-effect transistor based on a polythiophene organic semiconducting layer was developed. A modular enzymatic biosensor for glucose and urea, with a linear response in the range between 10-6 and 10-3 mol/L, was achieved. This biosensor relies on the immobilization the enzymes on gold rods, used as gate electrodes in the devices. The use of the bioreceptors proved to be selective and cross-selective in the devices. The possibility of exchanging the modified gate electrode to detect specific analytes using the same device system allows the modular sensor to be reused and applied for a broad range of applications. Which is the case for explosives molecules, TNT and DNT, biosensor fabricated in the same terms. This biosensor relies on the immobilization of specific binding peptides for TNT and DNT on the gold rod